Handedness-dependent quasiparticle interference in the two enantiomers of the topological chiral semimetal PdGa - Sessi, Paolo; Fan, Feng-Ren; Kuester, Felix; Manna, Kaustuv; Schroter, Niels B. M.; Ji, Jing-Rong; Stolz, Samuel; Krieger, Jonas A.; Pei, Ding; Kim, Timur K.; Dudin, Pavel; Cacho, Cephise; et al. (Nature Communications, 2020)
It has recently been proposed that combining chirality with topological band theory results in a totally new class of fermions. Understanding how these unconventional quasiparticles propagate and interact remains largely unexplored so far. Here, we use scanning tunneling microscopy to visualize the electronic properties of the prototypical chiral topological semimetal PdGa. We reveal chiral quantum interference patterns of opposite spiraling directions for the two PdGa enantiomers, a direct manifestation of the change of sign of their Chern number. Additionally, we demonstrate that PdGa remains topologically non-trivial over a large energy range, experimentally detecting Fermi arcs in an energy window of more than 1.6 eV that is symmetrically centered around the Fermi level. These results are a consequence of the deep connection between chirality in real and reciprocal space in this class of materials, and, thereby, establish PdGa as an ideal topological chiral semimetal.
CRIS-Team Scopus Importer:2022-04-14